Proceso de atención de enfermería en prematuro de 33 semanas con síndrome de dificultad respiratoria. - Jiménez Ortiz, Joselin Nicol (2021)
The main objective of the present work is to develop the nursing care process in a 33-week premature infant with respiratory distress syndrome who was transferred to the Neonatal Intensive Care Unit where it was stabilized, placing a nasal cannula at 2ltxmin, to avoid dryness in the mucosa and endogenous hypothermia. Likewise, the newborn was placed in a distress position, to open the epiglottis and improve gas exchange. Strict monitoring of vital signs was required, emphasizing the respiratory rate, temperature, and the administration of medications. Achieving that the independent and interdependent nursing interventions obtained an effective result. However, my patient remained hospitalized because his care is complex and requires trained personnel with sufficient knowledge and skills, for optimal care during his hospital stay, in order to reintegrate him into the community.